Fatores decisórios no processo de compra de reprodutores bovinos de corte em leilões no Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2012)
This study aimed to characterize the deciding factors in the buying process bulls of European breeds and synthetic sales in Rio Grande do Sul and its influence on the selling price. Were collected in the course of the auction number and the values of stallments final value of the sale of breeding stock, city of buyers number during the period from September 2011 to May 2012, on television and in preseutial sales. These data were compared with information from the sales catalogs of animals, such as race, hair color, scrotal circumference and age in months. Data were analyzed using analysis of variance and regression analysis. It was observed that the larger the size of scrotal circumference, the higher the sales price of the bulls. The older players were sold at best prices in relation to a young age. The number of stallments influenced the final value of animals for the Aberdeen Angus, Red Angus and Hereford, and there was an increase in value for the first two when the number of plots was 17. In Hereford there was a decrease in value when the final installment on 17 times.
Keywords: Comercialização; Melhoramento; Mercados; Genético; Touros; Commercialization; Breeding; Markets; Bulls; CNPQ::CIENCIAS AGRARIAS